Anxiety in speaking English among secondary school students: A case study / Norazah Hassan - Hassan, Norazah (2012)
The effects of second or foreign language anxiety are particularly evident in the language classroom. In this study, the focus was on communication apprehension, the main component of foreign language anxiety. Hence, this study was carried out to examine the perceptions of secondary school students towards learning and speaking English. Specifically, the objectives of the study were to investigate students' anxiety level in speaking English as second language and to identify the sources that contribute to speaking during the language lesson. A combination of quantitative and qualitative technique was employed to investigate these issues. A total of 230 Form four students of one identified secondary school at Taman Melawati, Gombak, Kuala Lumpur participated in the survey and 8 of them were interviewed to further strengthen and verify the findings of the survey. The sampling of participants was done through purposive sampling in order to select information rich cases. The study revealed that 1) secondary school students experienced low to moderate level of speaking anxiety 2) the students reported to be most anxious when giving oral presentation and role-play in front of the class and 3) five themes such as fear of making mistakes and apprehension about evaluation of others toward their speaking acts, language teacher's roles and classroom environment, pedagogical practices and classroom activities, linguistic difficulties: pronunciation, grammar, vocabulary and variations in individuals were identified as various sources of speaking anxiety during English lessons. Some implications for the students and language teachers are also stated briefly. Finally, some recommendations are suggested for practices and future study.